2016
DOI: 10.1099/ijsem.0.001248
|View full text |Cite
|
Sign up to set email alerts
|

Vitellibacter aquimaris sp. nov., a marine bacterium isolated from seawater

Abstract: A Gram-staining-negative, aerobic, yellow-orange-pigmented, rod-shaped bacterium designated D-24 T was isolated from seawater from sandy shoreline in Johor, Malaysia. The genus Vitellibacter is a member of the family Flavobacteriaceae in the phylum Bacteroidetes. The genus was first proposed by Nedashkovskaya et al. . Members of this genus are typically Gram-staining-negative, rodshaped, aerobic bacteria that have been isolated from marine environments, except for strain V. soesokkakensis RSSK-12 T which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The predominant cellular fatty acids (>10 % of total fatty acids) of strain S1-10 T were iso-C 15 : 0 (43.2 %) and anteiso-C 15 : 0 (21.3 %). Thus, the fatty acid profiles of strain S1-10 T resembled those of other Aequorivita species [9,31,32]. However, strain S1-10 T contained lower amounts of iso-C 15 : 1 G and iso-C 15 : 0 and higher amounts of anteiso-C 15 : 0 compared to A. viscosa DSM 26349 T .…”
Section: Physiology and Chemotaxonomymentioning
confidence: 81%
See 1 more Smart Citation
“…The predominant cellular fatty acids (>10 % of total fatty acids) of strain S1-10 T were iso-C 15 : 0 (43.2 %) and anteiso-C 15 : 0 (21.3 %). Thus, the fatty acid profiles of strain S1-10 T resembled those of other Aequorivita species [9,31,32]. However, strain S1-10 T contained lower amounts of iso-C 15 : 1 G and iso-C 15 : 0 and higher amounts of anteiso-C 15 : 0 compared to A. viscosa DSM 26349 T .…”
Section: Physiology and Chemotaxonomymentioning
confidence: 81%
“…Hahnke et al [3] proposed to place Vitellibacter into Aequorivita and to emend the description of Aequorivita accordingly in 2016. At that time, the paper describing V. aquimaris was just published [31] and V. todarodis has not been described [32]. The reconstructed phylogenetic trees based on the NJ and ML algorithms revealed that V. aquimaris and V. todarodis were grouped with the members of the genus Aequorivita.…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
“…Basonym: Vitellibacter aquimaris Thevarajoo et al 2016 The description is the same as for Vitellibacter aquimaris [10]. The type strain is D-24 T =KCTC 42708 T =DSM 101732 T .…”
Section: Description Of Aequorivita Aquimarismentioning
confidence: 99%
“…The proposed names of type species Vitellibacter vladivostokensis KMN 3516 T [5], Vitellibacter aestuarii JC2436 T [6], Vitellibacter soesokkakensis RSSK-12 T [7], Vitellibacter nionensis VBW088 T [8] and Vitellibacter echinoideorum CC-CZW007 T [9], were amended as Aequorivita vladivostokensis KMN 3516 T , Aequorivita aestuarii JC2436 T , Aequorivita soesokkakensis RSSK-12 T , Aequorivita nionensis VBW088 T and Aequorivita echinoideorum CC-CZW007 T , respectively [4]. Two recently identified species in the genus of Vitellibacter, Vitellibacter aquimaris [10] and Vitellibacter todarodis [11], were not classified into the genus Aequorivita, even though they phylogenetically grouped with those type strains being moved to the genus Aequorivita from the genus Vitellibacter. In this study, the novel strain q18 T , isolated from the estuarine sediment of the Pearl River in China (113.7145° E, 22.1221° N) at the depth of 8 m, was characterized using a polyphonic approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation